Very practical and selective method for PMB protection of alcohols - Chavan, Subhash P.; Harale, Kishor R. (Tetrahedron Letters, 2012)
A very simple, practical and efficient one-step heterogeneous protocol for the PMB protection of alcohols using Amberlyst-15 has been developed. The stability and hazard issues regarding PMBCI and PMBBr are totally avoided by directly using anisyl alcohol for the protection. Alcohols are protected in very good yields. The selective mono-PMB protection of diols as well as di-PMB protection of diols was achieved in good yields, along with the demonstration of recyclability of the catalyst. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: 4-Methoxybenzyl alcohol; 4-Methoxybenzyl protection; Amberlyst-15; Di-PMB protection; Mono-PMB protection